2014
DOI: 10.1111/maec.12125
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term demographic and reproductive trends in Ciona intestinalis sp. A

Abstract: Ciona intestinalis sp. A (Tunicata, Ascidiacea) is a marine invertebrate with a widespread distribution and high invasive potential, yet little is known about its ecology. Here, the macrodynamics of demographic and reproductive trends were first determined using archive data covering 2002–2012. Species abundance in the central Tyrrhenian Sea (Campania, Italy ‐ NW Mediterranean) displayed Poisson distribution across 2002–2008, massive die‐off in 2009/2010 and population recovery in 2011/2012. We defined the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Seawater temperature greatly influences the development, growth and survival of C intestinalis spp. (Dybern 1965;Marin et al 1987), with species A and species B reported as warm-water and coldwater species, respectively (Procaccini et al 2011;Caputi et al 2014). We observed higher growth rates at 17°C, for species A than species B during laboratory experiments (data not shown), confirming previous findings (Petersen et al 1995) based on the growth rate of the nominal species C. intestinalis in localities where only species A or species B are now reported [e.g.…”
Section: Seasonal Variation In Species Abundance: the Outcome Of Compsupporting
confidence: 93%
See 1 more Smart Citation
“…Seawater temperature greatly influences the development, growth and survival of C intestinalis spp. (Dybern 1965;Marin et al 1987), with species A and species B reported as warm-water and coldwater species, respectively (Procaccini et al 2011;Caputi et al 2014). We observed higher growth rates at 17°C, for species A than species B during laboratory experiments (data not shown), confirming previous findings (Petersen et al 1995) based on the growth rate of the nominal species C. intestinalis in localities where only species A or species B are now reported [e.g.…”
Section: Seasonal Variation In Species Abundance: the Outcome Of Compsupporting
confidence: 93%
“…The six sampling dates correspond to at least six different adult generations in European waters (e.g. Dybern 1965;Caputi et al 2014). In each locality, ca.…”
Section: Methodsmentioning
confidence: 99%
“…No C. robusta population inhabits close‐by surroundings of the Fusaro Lagoon, and the closest known population (Castel Volturno) is located ca. 20 km north along the Tyrrhenian Sea coast (Caputi et al, ). However, the lagoon is used for mussel cultivation, making services for mussel growing, transport, and harvesting possible recruiting sources.…”
Section: Discussionmentioning
confidence: 99%
“…Ascidians are benthic animals that populate coastal marine habitats with strong natural fluctuations of physico‐chemical parameters and high levels of pollution (Caputi, Crocetta, Toscano, Sordino, & Cirino, ; Carver, Chisholm, & Mallet, ; Dybern, ; Lambert, ; Simkanin, Davidson, Dower, Jamieson, & Therriault, ). These invertebrates are non‐selective filter feeders that uptake and bioaccumulate metals and other pollutants from the environment (Ignatiades & Becacos‐Kontos, ; Papadopoulou & Kanias, ; Radford, Hutchinson, Burandt, & Raftos, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation